Caries status and proximal lesion behaviour during a 6-year period in young adult Danes: An epidemiological investigation (2010)
Studies have indicated that many initial proximal caries lesions progress and are eventually restored even if the patients have been under comprehensive preventive programmes. The objectives of the study were (1) to describe the 1996-year baseline caries status of male Danish conscripts and (2) to assess their early proximal lesions 6-year behaviour. In 1996, all 20-year-old conscripts at Central Barrack Birkerød (n = 115) went through an oral examination, including visual surface-level fillings' recording and a radiographic examination with bitewing radiographs that assessed the proximal-surface caries and restoration patterns. After 6 years, the behaviour of proximal lesions was studied in 73 of these subjects, and oral health habits were assessed through a questionnaire. Mean number of filled surfaces was 7.5, of which 23% were posterior proximal. Radiographically, the mean number of proximal lesions was 5. 5. Over the 6-year period, there was progression of lesions into deeper radiolucencies or fillings in 57% of cases. The questionnaire showed a poor compliance with regular flossing/tooth-stick use (18%). Based on these results, more efficacious preventive measures seem to be needed for proximal surfaces. © 2009 Springer-Verlag.